Nurses’ perceptions of job security and performance: A comparative study between governmental and private hospitals - Islam Oweidat; Ghada Abu Shosha; Raghad Al-Harazneh; Khalid Al-Mugheed; Majdi Alzoubi; Amany Anwar Saeed Alabdullah; Sally Mohammed Farghaly Abdelaliem (PLoS ONE, 2025)
Aim Job security and performance are crucial needs for nurses, greatly influencing their motivation and commitment to work. This study seeks to examine Jordanian nurses’ perceptions of job security and employee performance and to compare these factors between government and private hospitals. Design A descriptive, comparative cross-sectional design was used for the study. Methods The study was conducted in two government and two private hospitals. A total of 156 nurses were conveniently sampled to participate. Data were collected using the Job Security Questionnaire and the Six-Dimension Scale of Nursing Performance. Results The mean job security score was 3.26, indicating a moderate level of job security. The mean employee performance score was 2.68, reflecting a high level of job performance. Nurses in private hospitals had significantly higher scores in both job security (t =  -5.53, p <  0.001) and employee performance (M =  2.53, SD ±  0.53) compared to nurses in government hospitals. Conclusion Nurses with moderate job security levels achieved high job performance scores. Private hospitals demonstrated higher job security and employee performance levels than government hospitals. Future research could investigate specific aspects of the Jordanian nursing work environment that may contribute to the differences observed in job security and employee performance.